Society and city in times of Philip II and the construction of the Viceroyalty of Peru. Notes on the Indians of Catacaos and the destruction of Payta by Cavendish (1587) - Espinoza Claudio, César (2021)
This paper presents the colonial structure built by viceroys in Piura to examine the social situation experienced by the people and the indigenous community of Catacaos during the last third of the sixteenth century. We describe and analyze the attack and destruction of the city and port of Payta in 1587, which is a political event that allows us to understand the functioning of the viceregal system, the social patterns, and organizations adopted by the indigenous people of Catacaos to adapt to a political system in the process of construction. Finally, we focus on the role of the colonial structures introduced by Philip II in the Corregimiento of Piura. In this sense, we delve into the social process experienced by Catacaos, among other indigenous peoples, to ensure the overland and maritime trade of silver from Potosi in northern Peru and the reinforcement of the city of San Miguel de Piura del Villar in 1588.